Barriers to effective civil society organisations : political, social and financial shifts - Natil, Ibrahim; Malila, Vanessa; Sai, Yousef (Abingdon, Oxon ; New York : Routledge, 2021)
"This book provides an insight into the historical changes and present-day circumstances that have influenced, and continue to influence, the development and future of civil society. Civil society organisations (CSOs) play a crucial role in international development, however their impact on policy and practice is limited by a range of shifts across their political, social and financial landscapes. Barriers to Effective Civil Society Organisations is divided into three parts addressing each of these shifts in turn, and places particular emphasis on civil society actors linked not only by political constraints, but also by ethnic and cultural diversities that are crucial markers of political and social identity. This book draws on case studies from across Latin America, Africa, MENA and Ireland to highlight how CSOs in these countries are shaped by, and react to, shifting challenges. Reflecting on solutions for the sector, the authors provide an understanding of the various 'self-accommodation' policies and techniques employed by CSOs in order to continue their services and increase their credibility across global contexts. Aimed at researchers, policy makers and CSO/NGO workers looking to better understand the current state and future of the sector from the perspective of emerging scholars working in these regions, and in the Global South in particular, this innovative book is a celebration of the important work of CSOs and a reaffirmation of their right to sit at the policy table"--
Introduction / Ibrahim Natil -- Introducing barriers to effective civil society organisations / Ibrahim Natil -- Africa CSOs civic spaces : bridging the information gap through social media / Vanessa Malila -- The changing civil society and the hybrid regime in Iran / Mohsen Moheimany and Alireza Najafinejad -- Reinvention of nationalism and the moral panic against foreign aid in Egypt / Ahmed El Assal and Amr Marzouk -- Civil society in the Gaza Strip : Qatari humanitarian aid / Ola Alkahlout -- NGO's rights-based approach between contextual appropriateness and political transformation in neopatrimonial in Cambodia / Rikio Kimura -- Civil society and left-wing governments in Latin America : the limits of influence / Chris O'Connell -- Shifting landscape in Morocco : civil society activism in post 2011 uprisings / Mohammed Yachoulti -- A case study of two Irish faith-based CSOs / Youcef Sai -- Conclusion: Implications and future direction / Ibrahim Natil.
OCLC-licensed vendor bibliographic record.
Keywords: Civil society -- Developing countries -- Case studies; Civil society -- Ireland -- Case studies; Non-governmental organizations -- Developing countries -- Case studies; Non-governmental organizations -- Ireland -- Case studies; POLITICAL SCIENCE / Political Freedom & Security / Civil Rights; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Public Policy / Social Policy